“Standing in the Breach”: Turning Away the Wrath of God - Schroeder, Christoph (Interpretation, 1998)
Wrath is often understood as the dark and irrational side of God that can be appeased only through the offering of a scapegoat. The metaphor of a human “standing in the breach” defies this common understanding and points to the moral dimension of God's wrath.